The Relationship between Economic Growth, Renewable Energy, and CO2 Emissions: Evidence from Panel Data Approach - Mahmoodi, Majid (International Journal of Energy Economics and Policy, 2017)
The aim of the present study is to examine the relationship between economic growth, renewable energy (RE) and carbon dioxide emission (CO2) for a panel of 11 developing countries over the period 2000–2014. The panel cointegration and panel vector error correction model causality is employed to examine the long-run and causal relationships between the variables. The results of Kao and Pedroni panel cointegration test indicate the existence of long-run relationship between economic growth, RE and CO2 emissions. Also the panel causality results indicate bidirectional causality between RE and CO2 emission, bidirectional causality between gross domestic product (GDP) and CO2, and unidirectional causality from GDP to RE. Furthermore, the results of panel dynamic ordinary least squares estimates show the positive impact of economic growth on CO2 emissions and negative impact of RE on CO2 emissions. Keywords: Economic Growth, Renewable Energy, CO2 Emissions, Panel Data JEL Classifications: C33, O44, Q20